Planning Of Tozer Methodology Master Plan In Educational Of Information And Communication Technology (A Case Study At PT Pesona Edu Solution Jakarta) - Hartati, Tri (Teknik dan Ilmu Komputer, 2017)
AbstractÃÂ In this information age, business activities of an organization cannot be separated from the role of information systems (IS) and information technology (IT). IS is a reliable tool to win the competition in the industry. Strategic planning of IS/IT is a step taken by a company that wants a better corporate environment in the future. PT. Pesona Edu Solution is an institution that provides computer-based education services. In planning the strategic information systems and information technology in the company, the researcher used Tozer methodology. It consists of five phases that define the context and scope, specify the information and business, evaluate the suitability of the system with current business needs, define strategic solutions, and prepare and conduct the implementation plan. This research results in the implementation of the master plan of the proposed framework providing strategic planning of Information Systems/Information Technology that can be applied on PT. Pesona Edu Solution.ÃÂ Keywords: master plan, strategic planning information systems/information technology, tozer methodology